Pengembangan Buku Saku Berbasis Inkuiri pada Materi Mengidentifikasi Unsur-Unsur Drama di Kelas VIII SMP Negeri 2 Hiliduho - Restu Krismon Putra Zebua; Riana; Lestari Waruwu (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The purpose of this research is to develop a decent, practical, and effective Inquiry-based pocketbook learning media. This type of research is development research using the ADDIE model which consists of analysis (Analyze), design (Design), development (Development), implementation (Implementation), evaluation (Evaluation). The research instruments used were questionnaires validating material experts, linguists, and design experts, as well as student response questionnaires and the effectiveness of student learning outcomes. The results of this research are in the form of inquiry-based pocketbook products on the material of identifying the elements of drama. Material expert assessment in revision I reached 71%, in revision II reached 96.3%, with very decent criteria. The assessment of linguists in revision I reached 82.1%, in revision II it reached 100%, with very decent criteria. The design expert's assessment in revision I was 40%, in revision II it reached 98.33% with very feasible criteria. The results of the assessment on the student response questionnaire in the small group trial obtained a score of 95.5% in the very practical category. In the field test, a score of 87.3% was obtained in the very practical category. Assessment of student learning outcomes tests obtained a percentage of classical completeness in 100% small group trials and 100% field trials with very effective criteria. From the results of the research above, pocketbooks are feasible, practical, and effective for use in the learning process.